Establishing ICT compentency standard for Malaysian teachers using the Delphi technique - Fong, Soon Fook; Boey, Gerard Kong Hoong; Azidah Abu Ziden; Mohd Hamdan Adnan (American Scientific Publishers, 2016)
Technology has tremendous potential to enhance learning across all disciplines and inculcate critical and creative thinking skills. However, in spite of huge investment on Information and Communication Technology over the past decade in various education initiatives, the potential of technology usage in Malaysian schools have not reached the desired level among teachers and students. What is the missing link for the realization of the expected return-of-investment? The establishment of the Educational Technology Competency Standards for 21st Century Malaysian Teachers using the Delphi technique will allow authorities to review and regulate ICT-related training curriculum to uplift the standards of teaching and learning to be in compliance with the Malaysia National Education Blueprint 2013–2025.